The state of the art in intrusion prevention and detection - Pathan, Al-Sakib Khan (Auerbach Publications, CRC Press, Taylor & Francis Group, USA, 2014)
Most of the security threats in various communications networks are posed by the illegitimate entities that enter or intrude within the network perimeter, which could commonly be termed as intruders. Sometimes a legitimate entity in a system could also be compromised in some way so that an attacker-intended task could be performed for breaching security of the system. To tackle intrusion of various kinds, we commonly hear about Intrusion Detection System (IDS) and Intrusion Prevention System (IPS), or a combination of both called, IDPS (Intrusion Detection and Prevention System). The main task of an IDS is to defend a computer system or computer network by detecting an attack and possibly repealing it. Successful detection of hostile attacks depends on the number and type of appropriate actions. On the other hand, intrusion prevention requires a well-selected combination of ‘baiting and trapping’ aimed at the investigations of threats. Diverting the intruder’s attention from protected resources is another task. Both the real system and a possible trap system are constantly monitored.